The community resilience reader : essential resources for an era of upheaval - Lerch, Daniel (Washington : Island Press, 2017)
'The sustainability challenges of yesterday have become today's resilience crises. National and global efforts have failed to stop climate change, transition from fossil fuels, and reduce inequality. We must now confront these and other increasingly complex problems by building resilience at the community level. But what does that mean in practice, and how can it be done in a way that's effective and equitable? The Community Resilience Reader offers a new vision for creating resilience, through essays by leaders in such varied fields as science, policy, community building, and urban design. The Community Resilience Reader combines a fresh look at the challenges humanity faces in the 21st century, the essential tools of resilience science, and the wisdom of activists, scholars, and analysts working with community issues on the ground. It shows that resilience is a process, not a goal; how resilience requires learning to adapt but also preparing to transform; and that resilience starts and ends with the people living in a community. Despite the formidable challenges we face, The Community Resilience Reader shows that building strength and resilience at the community level is not only crucial, but possible.'--Publisher's website.
Introduction / Daniel Lerch -- Six foundations for building community resilience / Daniel Lerch -- PART 1. Understanding our predicament. The environmental crisis: the needs of humanity versus the limits of the planet / Leena Iyengar -- The energy crisis: from fossil fuel abundance to renewable energy constraints / Richard Heinberg -- The economic crisis: the limits of twentieth-century economics and growth / Joshua Farley -- The equity crisis: the true costs of extractive capitalism / Sarah Byrnes and Chuck Collins -- The roots of our crises: does human nature drive us toward collapse? / William Rees -- PART II. Gathering the needed tools. Systems literacy: a toolkit for purposeful change / Howard Silverman -- A crash course in the science of sustainability / Margaret Robertson -- A crash course in the science of resilience / Brian Walker and David Salt -- Pulling it all together: resilience, wisdom, and beloved community / Stephanie Mills -- PART III. Community resilience in action. Energy democracy / Denise Fairchild and Al Weinrub -- Building community resilience at the water's edge / Rebecca Wodder -- Food system lessons from Vermont / Scott Sawyer -- Learning our way toward resilience / William Throop -- Beyond waste: sustainable consumption for community resilience / Rosemary Cooper -- Resilient streets, resilient cities / Mike Lydon -- Community resilience and the built environment / Daniel Lerch -- Conclusion: where to start / Asher Miller.
Includes bibliographical references and index.
Keywords: Community development -- Environmental aspects; Sustainable development; Energy policy -- Environmental aspects; Economic development -- Environmental aspects